Changing the Approach in Supporting and Advancing Underrepresented in Medicine (UIM) Medical Students - Abena Knight; Terry Kind; Gabrina Dixon; Natalie McKnight; Molly Rideout (Association of American Medical Colleges, 2024)
Introduction Research has shown the importance of diversity in improving patient care. Medical students from backgrounds underrepresented in medicine (UIM) face unique challenges, including minority tax, stereotype threat, and expectations to be the sole representative of their identity group. Mentors must be aware of these challenges and develop skills to address them. Methods We designed a 90-minute workshop about the challenges UIM students encounter in medical school and best practices in mentorship. Target audience and facilitators were undergraduate medical educators. Three videos and questions for case-based facilitated small-group discussion with medical school faculty and administrators were included. Using a retrospective pre-post design, we elicited participants' confidence level in recognizing and addressing issues UIM students may experience and plans to apply skills gained in the workshop. Results Workshop participants (N = 57) reported a mean increase in confidence rating of 20-26 points out of 100 for recognizing, identifying, and applying skills related to optimal UIM mentorship (mean confidence: 53-60 preworkshop, 79-81 postworkshop). Participants also reported a mean of 82 in readiness to apply skills learned. Participants rated the workshop a 4.6 in overall helpfulness on a 5-point Likert scale (1 = not helpful, 5 = extremely helpful). Discussion Health care professionals working with UIM medical students have an essential role in mentorship and support. This workshop provides a structured forum to discuss challenges and build awareness, comfort, and skills regarding engaging in meaningful discussions about race and the experiences of medical students, even when identities are incongruent.